2013
DOI: 10.1186/1475-2891-12-136
|View full text |Cite
|
Sign up to set email alerts
|

Daily milk intake improves vitamin B-12 status in young vegetarian Indians: an intervention trial

Abstract: BackgroundAsymptomatic Indian lacto vegetarians, who make up more than half of the Indian population in different geographic regions, have distinctly low vitamin B-12 concentrations than non- vegetarians. Vegetarians consume milk but it seems that the amount is not enough to improve vitamin B-12 status or vitamin B-12 concentration in milk itself may be low. The aim of this study was to determine if daily milk consumption can improve vitamin B-12 status.MethodsFifteen male and 36 female, young healthy post-gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 38 publications
7
36
0
Order By: Relevance
“…A study from China, found about one fourth of participants only consumed vegetables and fruits, [57]. However, another study from Malaysia noted that only the minority of university students devoted vegetables more than three times weekly [26].This finding in agreement with [51] and [64], who concluded that the acceptance of unhealthy eating habits along with college students, mainly with regard to the reduced utilization of fruit and vegetables.…”
Section: The Association Between Eating Habits and Body Mass Index Amsupporting
confidence: 81%
“…A study from China, found about one fourth of participants only consumed vegetables and fruits, [57]. However, another study from Malaysia noted that only the minority of university students devoted vegetables more than three times weekly [26].This finding in agreement with [51] and [64], who concluded that the acceptance of unhealthy eating habits along with college students, mainly with regard to the reduced utilization of fruit and vegetables.…”
Section: The Association Between Eating Habits and Body Mass Index Amsupporting
confidence: 81%
“…The deficiency of Cbl is defined by the serum concentrations <110 pmol/L [76,77], <127 pmol/L [78], <148 pmol/L [79,80], <150 pmol/L [81,82,83], <156 pmol/L [84,85], <220 pmol/L [86], <250 pmol/L [8]. The Institute of Medicine defined 120–180 pmol/L as a depletion range [25].…”
Section: Assessment and Diagnostic Markersmentioning
confidence: 99%
“…The increased plasma concentration of HCY and urinary or serum MMA can provide more detailed information on the deficiency condition. As for serum Cbl, the criteria for an excess of HCY are heterogeneous: >15 μmol/L [78,80,81,83,85,92], >12 μmol/L [18,76,77,84,86,91,93,94], >10 μmol/L [8]. In addition, there are different criteria of deficiency for serum MMA cutoffs ranging from >271 nmol/L to >376 nmol/L, with the former being most prevalent [18,81,82,84,85,93,94,95].…”
Section: Assessment and Diagnostic Markersmentioning
confidence: 99%
“…A study in Pune, India investigated supplementation with buffalo milk. 45 There was an increase in both serum B12 and holoTC concentrations and a decrease in plasma homocysteine concentrations in response to supplementation with 400 ml of buffalo milk (B12 content 2.5-3.8 μg/l) every day for 14 days for the 29 lactovegetarian participants with a serum B12 o 148 pmol/l. 45 Sustainability of intake for longer periods was not investigated, and buffalo milk has a higher B12 content than that recorded for cow's milk, but these findings are consistent with other published studies that report a high bioavailability of B12 from dairy products.…”
Section: Discussionmentioning
confidence: 89%